Optimalisasi Pertumbuhan dan Hasil Tanaman Padi Varietas Caredek Di Lahan Gambut akibat Pemberian Beberapa Dosis Kapur Dolomit - Ekawati, Fitri; Suliansyah, Irfan; Ardhana, Abdillah (Jurnal Agroekoteknologi, 2025)
Utilization of marginal land, such as peatlands, to increase national rice production needs to be done. This is because the need for rice consumption increases yearly, while many productive lands have been converted for settlements. The provision of amelioran dolomite lime on peatlands before cultivating rice plants can be done to overcome problems on peatlands. This study aims to see how the growth and yield responses of the Caredek variety of rice on peatlands are due to the administration of several doses of dolomite lime. The study used a Randomized Block Design consisting of 4 dolomite lime dose treatments, including 0 tons/ha, 5 tons/ha, 10 tons/ha, and 15 tons/ha. Each treatment was repeated 3 times. Data were analyzed using the F test at a 5% level, and the DNMRT test was continued at a 5% level if it showed a significantly different effect. The results showed that the administration of dolomite lime affected growth (plant height and leaf area index) but did not affect the yield of the Caredek variety of rice on peatlands. A dose of dolomite lime of 5 – 15 tons/ha is generally effective in increasing the growth and yield of Caredek variety rice plants on peatlands compared to not applying dolomite lime.